AUCTIONS WITH LEAKS ABOUT EARLY BIDS: ANALYSIS AND EXPERIMENTAL BEHAVIOR. (26th October 2020) - Fischer, Sven; Güth, Werner; Kaplan, Todd R.; Zultan, Ro'i
Abstract : In sequential first‐ and second‐price private value auctions, second movers are informed about the first movers' bid with commonly known probability. Equilibrium bidding in first‐price auctions is mostly unaffected, but there are multiple equilibria in second‐price auctions affecting comparative statics across price rules. We show experimentally that informational leaks in first‐price auctions qualitatively confirm the theoretical predictions. In second‐price auctions, we analyze and experimentally confirm the existence of focal equilibria, and provide evidence for individual consistency in equilibrium selection. ( JEL D44, C72, C91)